Teknologi Informasi Berbasis XBRL Meningkatkan Pengungkapan Pelaporan Keuangan - Rahmiyanti, Sev (Universitas Banten Jaya, 2024)
ABSTRACT For the purpose of public company financial reporting, XBRL technology has seen extensive adoption across a number of nations. Nevertheless, there has been a dearth of literature reviewing the research on XBRL technology's ability to enhance disclosure quality and its level of complexity. The purpose of this work is to use qualitative analysis and a literature study to make conclusions. Quicker data transmission and more efficiency are only two of the several benefits of the XBRL-based reporting system over its predecessors. Better disclosure and more openness are possible thanks to the XBRL reporting system, which is based on sophisticated information technology. Keywords: XBRL, taxonomy, transparency, disclosing financial reports